A numerical study of ultrasonic response of random cortical bone plates - Abdoulatuf, A.; Nguyen, V-H.; Desceliers, C.; Naili, S. (Vietnam Journal of Mechanics, 2017)
A probabilistic study on ultrasound wave reflection and transmission from cortical bone plates is proposed. The cortical bone is  modeled by an anisotropic and heterogeneous elastic plate sandwiched between two fluids and has randomly varied elastic properties in the thickness direction. A parametric stochastic model is proposed to describe the elastic heterogeneity in the plate. Reflection and transmission coefficients are computed via the semi-analytical finite element (SAFE) method. The effect of material heterogeneity on reflected and transmitted waves is investigated from a probabilistic point of view. The parametric study highlights effects of the uncertainty of material properties on the reflection and transmission coefficients by varying the frequency, angle of incidence and bone thickness.